Mandarin Language Students Illocutionary Acts in Japanese Language Learning at the University of Sumatera Utara - Taulia Taulia; Laraiba Nasution (Politeknik Negeri Padang, 2021)
Speech acts play an essential role in language learning as an aspect that can improve a learner's ability to speak orally. In this research, illocutionary speech-acts were described in the Japanese language learning process for students of the Mandarin Language Department, Faculty of Cultural Sciences, University of Sumatera Utara. This research is qualitative. The data are speech acts in the lecture process in class, especially in the discussion. The data sources were 40 fourth-semester students of the Mandarin Language Department. The theory used was the Searle speech act theory. Data collection techniques were carried out through observation, recording , and note-taking techniques. Data analysis techniques were carried out applying Miles & Huberman's opinion by condensing data through transcription of recorded data into written form, identifying forms, speech act functions, data presentation, and concluding. As a result, there were forms of illocutionary speech acts, namely directive, expressive, and declarative. Furthermore, the purpose used in class was in directive speech acts which were to order, ask, invite (engage). In other words, in expressive speech-act was praising, and in declarative speech-act was prohibiting. In conclusion, Japanese speech acts in Japanese class occured between lecturers and students and only consisted of several types of speech acts due to students' limited mastery of Japanese.